Impersonals and other agent defocusing constructions in French - Achard, Michel, 1959- (Human cognitive processing ;, 2015)
This book investigates French impersonals as a functional category. Any structure whose agent is defocused and whose predicate describes a situation stable enough to be generally available should be considered impersonal. In addition to il impersonals, the category also includes demonstrative (ce/ça), middle (se), and indefinite (on) structures. These different forms belong to the same functional category because they systematically code general and predictable events that cannot be imputed to a specific cause. Because generality and predictability are gradual notio.